SOSIALISASI PROTOKOL KESEHATAN COVID 19 MENGGUNAKAN STRATEGI KOMUNIKASI DI WILAYAH KERJA PEMERINTAH DESA GOLONG - Agung Saukani Dewantara; Shinta Desiyana Fajarica; Yulanda Trisula Sidarta Y. (Jurnal Interaktif: Warta Pengabdian Pendidikan, 2022)
COVID-19 is an infectious disease caused by a newly discovered coronavirus. This new virus and the disease it causes were unknown before the outbreak started in Wuhan, China, in December 2019. COVID-19 has now become a pandemic that has occurred in many countries around the world. Therefore, socialize the importance of using the COVID-19 health protocol now. This is very important, because not all people understand about this disease. The socialization that was carried out in Golong Village was carried out to provide understanding to the community that it was important to comply with the COVID-19 health protocol, such as wearing masks, maintaining distance, and washing hands. This service aims to provide an understanding of the importance of using the COVID-19 health protocol to the people in Golong Village. The target of this socialization is the whole community of Golong Village, especially children and elderly parents. A good communication strategy is needed so that the socialization provided is easy to understand.